Gangguan Fase Generatif Akibat Genangan Berulang pada Cabai Rawit - Muhammad Rizza Pahlevi; Hesti Kurniahu (Fakultas Matematika & Ilmu Pengetahuan Alam - Universitas Islam Malang, 2022)
Cayenne pepper is a cultivated plant that is susceptible to flooding caused by poor drainage systems on agricultural land. Plants are more sensitive to flooding in the generative phase. The generative phase of the plant begins when it is approaching the flowering process until it bears fruit. The objectives of this study to examined the impact of cayenne pepper cultivar selection and repeated flooding on the average flowering time, fruiting time and the percentage of fruit loss. Three types of cayenne pepper cultivars were used, namely Mhanu XR, Sret and Cakra Hijau. Repeated flooding treatments were flooding 1 time, 2 times, 3 times and control without flooding. The data were analyzed using a two-way ANOVA statistical test. The results indicated that cultivar selection had a significant influence on the average flowering time, fruiting and fruit loss percentage. Meanwhile, repeated flooding and interaction between cultivars and repeated flooding had no significant effect on flowering time, fruiting and the percentage of fruit loss. The conclusion shows that the three cultivars of cayenne pepper have different responses to repeated flooding on the parameters of the time of flowering, fruiting and the percentage of fruit loss with the most adaptive cultivar, namely Cakra Hijau. The Cakra Hijau cultivar can be a good candidate in poor drainage than the Mhanu XR and Sret cultivars.